2015
DOI: 10.1097/inf.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Bacteremia in Children

Abstract: The incidence of SAB tripled during the years studied but remained stable in the last period. Antimicrobial resistances did not increase. Although a decrease in mortality was documented, approximately half the 30-day cumulative mortality was caused by SAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
5
23
1
9
Order By: Relevance
“…Of note, almost 80% of our patients had CVC. The primary origin of SAB in one study was from CVC and prolonged bacteremia was also reported in the presence of CVC [13,22]. Unsuspected foci may contribute significantly to the mortality and morbidity of SAB as failure to identify complications timely, particularly endocarditis and vertebral osteomyelitis, may result in calamitous outcomes, including neurologic events, multi-organ failure, paralysis, and death [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, almost 80% of our patients had CVC. The primary origin of SAB in one study was from CVC and prolonged bacteremia was also reported in the presence of CVC [13,22]. Unsuspected foci may contribute significantly to the mortality and morbidity of SAB as failure to identify complications timely, particularly endocarditis and vertebral osteomyelitis, may result in calamitous outcomes, including neurologic events, multi-organ failure, paralysis, and death [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The morbidities associated with S. aureus bacteremia (SAB) consist of focal and systemic complications that may occur at any bodily site with MRSA twice as likely as methicillin-susceptible S. aureus (MSSA) to cause complications in SAB [12]. Different studies have evaluated complications in children with SAB, including osteomyelitis, septic arthritis, pneumonia, meningitis, infective endocarditis, and toxic-shock syndrome [13][14][15][16][17][18][19][20][21][22][23]. Other complications, including septic shock, respiratory distress syndrome, and splenic abscess have not been extensively described in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, los factores de riesgo asociados a letalidad, como la edad ≥ 8 años, las formas clínicas de sepsis/bacteriemia, meningitis y neumonía, fueron similares a lo informado por otros estudios. 4,[33][34][35] Cabe destacar que la presencia de factores predisponentes, el sexo y las infecciones graves de tejidos blandos (fascitis y miositis) no se asociaron a mayor letalidad.…”
unclassified
“…Cases may be isolated or occur as part of an outbreak, and affect children of any age. During adolescence, SA is the most common causative agent of communityacquired sepsis, [3][4][5] probably due to transmission in dressing rooms used in relation to sport activities.…”
mentioning
confidence: 99%
“…pyomyositis, osteomyelitis, septic arthritis, or endocarditis, and as severe conditions, such as necrotizing Community-acquired Staphylococcus aureus, a recent problem pneumonia, pleural empyema, and sepsis, all associated with high morbidity and mortality. 4,5 Then, CA-MRSA infections turned into an emerging problem due to its elevated virulence and high dissemination power. This problem was approached in an article published in the Archivos Argentinos de Pediatría in 2008.…”
mentioning
confidence: 99%